Bhopal Disaster Gas Victims’: Trauma Before & During the COVID-19 Pandemic - Mandal, Monalisha; Rahman, Md. Mojibur (Problemy Ekorozwoju, 2021)
Many studies, reports, books, narratives, and surveys have focused on the disputable picture of the sustainable development of victims of the Bhopal Gas Disaster to understand the trauma, faced by the victims and survivors before and during the COVID-19 period. Traumatic accidents fundamentally shatter the time-based experience of humans between the present and the past. The poisonous night not only had an intense effect on their way of life, but also had an acute impact on their understanding of how to deal with problems. However, another whammy COVID-19 makes their lives more traumatized, unsustainable, and also the victims of another catastrophe. The researchers of the present study have attempted to focus on the traumatic conditions and lessons faced by the Bhopal Gas Victims. In short, the present study puts the focus on the disputable record of sustainable development of the Bhopal Gas Victims in duration, from 1984 to the COVID-19 period, through an analysis of different studies.